The Portrayals of Amistad Case in Amistad (1997) Film: A New Historicism Study - Amalia, Anisa; Muhajir, Fatimah; Sudirman, Eka Pratiwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Hollywood cinema during the late 20th century started to re-create the historical events of African-American’s past, make it a historical films genre, and deliver the history of Amistad case about Mende’s mutiny in Amistad film. The film becomes receptive to addressing another side of Africans slavery history in the western country. To understand the historical event, the researcher sees it through the New Historicism’s lens as an approach of this research. This research uses a qualitative method through collecting the data from audio-visual materials and document analysis to answer the research questions. The research questions of this research are; first, how is the comparison of the Amistad case event in the Amistad film and historical records. Secondly, why does the Amistad film portray a different angle of the Amistad case. Seeking the answers, the researcher compares the representations of the past event and found the contradictory the Amistad film and the historical. The results of this research indicate that Amistad film presents events about the Amistad case differently to opposed the historical records and get positive results through adding moral values from historical events.Sinema Hollywood pada akhir abad ke-20 mulai mengkreasi ulang peristiwa sejarah masa lalu orang Afrika-Amerika dengan menjadikannya genre film sejarah, dan menyampaikan sejarah kasus Amistad tentang pemberontakan Mende dalam film Amistad. Film ini menjadi reseptif untuk membahas sisi lain dari sejarah perbudakan Afrika di negara barat. Untuk memahami peristiwa sejarah, penulis melihatnya melalui kacamata New Historicism sebagai pendekatan penelitian ini. Penelitian ini menggunakan metode kualitatif melalui pengumpulan data dari bahan audio visual dan analisis dokumen untuk menjawab permasalahan penelitian. Rumusan masalah penelitian ini adalah; pertama, bagaimana perbandingan kasus Amistad dalam film Amistad dan catatan sejarah. Kedua, mengapa sutradara, produser, dan penulis naskah menampilkan sudut pandang cerita film Amistad yang berbeda dari catatan sejarah. Untuk menjawabnya, penulis membandingkan representasi peristiwa masa lalu dan menemukan kontradiksi antara film Amistad dan catatan sejarah. Hasil penelitian ini menunjukkan bahwa film Amistad menyajikan peristiwa tentang kasus Amistad secara berbeda untuk menentang catatan sejarah dan mendapatkan hasil positif melalui penambahan nilai moral dari peristiwa sejarah.